HUBUNGAN MOTIVASI DENGAN PELAKSANAAN MOBILISASI DINI PADA PASIEN POST OPERASI FRAKTUR EKSTREMITAS BAWAH DI RUMAH SAKIT UMUM DAERAH MEURAXA BANDA ACEH - Nurul Izzah; Isneini Isneini; Sofyan Sufri; Setio Budi Raharjo (Poltekkes Kemenkes Aceh, 2023)
The incidence of fractures in Indonesia continues to increase with the highest cases being lower extremity fractures with a prevalence rate of 67.9%. Complications can occur due to one of the factors, namely the lack of patient mobilization. This study aims to determine the relationship between motivation and the implementation of early mobilization in postoperative lower extremity fracture patients at Meuraxa Hospital. The design of this study used a descriptive cross-sectional study approach. The sample in this study used purvosive sampling with a total sample of 36 lower extremity fracture patients. The univariate and bivariate data analysis used the Chi Square statistical test. The results showed that the results of the chi square test with a p value of 0.003 (p <0.05). This shows that there is a relationship between patient motivation and the implementation of early mobilization in lower extremity post fracture patients at Meuraxa Hospital Banda Aceh 2021.